Pengaruh kualitas laporan keuangan, pemanfaatan teknologi, pengendalian internal dan sistem pelaporan terhadap akuntabilitas kinerja - Nuraeni, Iin; Pramita, Yulinda Devi; Afif, Naufal (Universitas Muhammadiyah Magelang, 2023)
Abstract This study aims to empirically examine the effect of financial quality, utilization of information technology, internal control and reporting systems on the performance accountability of the government of Magelang Regency. The research population is OPD in Magelang Regency. This research was conducted in 24 OPD. The research sample is 75 respondents, obtained by purposive sampling technique. The research uses primary data in the form of answers from research questionnaires obtained from respondents who are the research sample. The analysis technique used in this study is data analysis using descriptive statistical tests, data quality tests consisting of validity and reliability tests and hypothesis testing using multiple linear regression analysis. From the results of data analysis, it can be concluded that internal control and the reporting system have a significant positive effect on performance accountability, while the quality of financial reports and the use of information technology have no effect on performance accountability. Keywords: quality of financial reports; use of information technology; internal control; reporting systems; performance accountability.